Protective Antibodies Against Influenza Proteins - Padilla-Quirarte, Herbey O.; Lopez-Guerrero, Delia V.; Gutierrez-Xicotencatl, Lourdes; Esquivel-Guadarrama, Fernando (Frontiers in Immunology, 2019)
The influenza A virus infection continues to be a threat to the human population. The seasonal variation of the virus and the likelihood of periodical pandemics caused by completely new virus strains make it difficult to produce vaccines that efficiently protect against this infection. Antibodies are very important in preventing the infection and in blocking virus propagation once the infection has taken place. However, the precise protection mechanism provided by these antibodies still needs to be established. Furthermore, most research has focused on antibodies directed to the globular head domain of hemagglutinin. However, other domains of HA (like the stem) and other proteins are also able to elicit protective antibody responses. In this article, we review the current knowledge about the role of both neutralizing and non-neutralizing anti-influenza proteins antibodies that play a protective role during infection or vaccination.